Spectrophotometric Method Development and Validation for Simultaneous Estimation of Nebivolol hydrochloride and Valsartan in Bulk and Combined Pharmaceutical Dosage Form in Release Media (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
A simple, rapid, precise, accurate and sensitive spectrophotometric method has been developed for the simultaneous estimation and validation of Nebivolol Hydrochloride (NEB) and Valsartan (VAL) in pure and combined tablet dosage forms. Pure drug samples of NEB and VAL were dissolved in 67 mM Phosphate buffer pH 6.8 with 0.5 % sodium dodecyl sulphate (SDS) and found to have absorbance maxima at 280 nm for NEB and 250 nm for VAL, respectively. The linearity lies between 10-70 μg/ml for NEB and 10-60 μg/ml for VAL in this method. The correlation coefficient (r2) was found to be 0.9965 for NEB and 0.9960 for VAL. The % recoveries obtained were 95.65 % – 109.85 % for NEB and 97.42 % – 101.43 % for VAL. The % RSD found 0.271 %-1.490 % for intraday and 0.334 %-1.917 % for interday for NEB and 0.188 %-0.944 % for intraday and 0.392 %-1.197 % for interday for VAL. The limit of detection and limit of quantitation for NEB were found to be 4.608 μg/ml and 13.965 μg/ml respectively and the limit of detection and limit of quantitation for VAL were found to be 4.348 μg/ml and 13.178 μg/ml respectively. Simultaneous calibration of both drugs in 67 mM Phosphate buffer pH 6.8 with 0.5 % SDS shows that λmax of one drug does not interfere on the λmax of other drug. Recovery study was performed to confirm the accuracy of the method. The results of analysis have been validated statistically by recovery studies as per International Conference on Harmonization guidelines. The method showed good reproducibility and recovery with % RSD <2. Hence, this proposed method was found to be rapid, specific, precise, accurate and can be successfully applied for the routine analysis of NEB and VAL in pure and combined tablet dosage form.